(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the adolescent age in the formation of the personality, its social and biological development, internal conflicts that occur in the person and the changes in the character traits of the teenager during the occurrence, transition, and intensification of the internal conflict are discussed abroad, Commonwealth of Independent States and the state of being studied by the scientists of our country.